Princess in the spotlight - Cabot, Meg (New York HarperCollins, 2001)
Having recently discovered she is the sole heir to the throne of a tiny European principality, fourteen-year-old Manhattan resident Mia writes in her journal about her attempts to cope with this news, as well as with more typical teenage concerns.
91658
Keywords: Princesses; Diaries; Schools; Identity; New York (N.Y.)